2012
DOI: 10.1634/theoncologist.2012-0186
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Geriatric Assessments in Predicting Treatment Tolerance and All-Cause Mortality in Older Patients With Cancer

Abstract: After completing this course, the reader will be able to:1. Describe the predictive value of geriatric assessments for survival in older cancer patients.2. Describe the predictive value of geriatric assessments for treatment tolerance (such as toxicity of chemotherapy and perioperative complications) in older cancer patients. Explain the concept of frailty compared to individual geriatric conditions.This article is available for continuing medical education credit at CME.TheOncologist.com. CME CME ABSTRACTBack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
101
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(107 citation statements)
references
References 90 publications
(48 reference statements)
2
101
1
1
Order By: Relevance
“…In our study, these were comorbidity, functional status, and nutritional status. However, the evidence regarding the predictive value of individual domains of the GA is still inconsistent [16]. In addition, some domains have obvious clinical value irrespective of predictive power.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, these were comorbidity, functional status, and nutritional status. However, the evidence regarding the predictive value of individual domains of the GA is still inconsistent [16]. In addition, some domains have obvious clinical value irrespective of predictive power.…”
Section: Discussionmentioning
confidence: 99%
“…However, two recent reviews conclude that the evidence is still conflicting and that further research is needed to establish the role of GA in predicting outcomes and affecting treatment decisions [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…However, various geriatric conditions appear to be of some value in predicting outcome in older adult patients with cancer [12]. One instrument that is often suggested as useful for obtaining a thorough overview of patients' health by determining the functional, cognitive and psychosocial status in addition to comorbidity, medication use and nutritional status, is the geriatric assessment [13,14].…”
mentioning
confidence: 99%
“…Low grip strength was reported to be the only frailty marker (of seven measured) to predict treatment toxicity in a prospective observational study of 112 patients with different types of cancer [26]. Hamaker et al [27] conducted a systematic search of studies on geriatric assessment in oncology, focusing on the association between baseline assessment and outcomes, and found that frailty was predictive of chemotherapy-induced toxicity; impairments in cognitive functions and activities of daily living were predictive of chemotherapy completion, and impairment in instrumental activities of daily living was predictive of perioperative complications. However, these results were too inconsistent to guide treatment decisions.…”
Section: Discussionmentioning
confidence: 99%